1996
DOI: 10.2307/2269492
|View full text |Cite
|
Sign up to set email alerts
|

Water Use by Tamarix Ramosissima and Associated Phreatophytes in a Mojave Desert Floodplain

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.. Ecological Society of America is collaborating with JSTOR to digitize, preserve and extend access to Ecological Applications.Abstract. Water use by the introduced shrub Tamari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
177
1
2

Year Published

2002
2002
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 206 publications
(196 citation statements)
references
References 34 publications
16
177
1
2
Order By: Relevance
“…The larger LAI, the higher ET. The same pattern was observed in arid regions of southwest USA (Sala et al, 1996). We analyzed the relationship of LAI and ET/ET 0 in GLE and LSP for both Tamarix stand and Populus stand.…”
Section: Key Control Factors On the Spatial Variations Of Etsupporting
confidence: 56%
“…The larger LAI, the higher ET. The same pattern was observed in arid regions of southwest USA (Sala et al, 1996). We analyzed the relationship of LAI and ET/ET 0 in GLE and LSP for both Tamarix stand and Populus stand.…”
Section: Key Control Factors On the Spatial Variations Of Etsupporting
confidence: 56%
“…Of further risk to riparian GDEs and agriculture, groundwater extraction and land use change threaten riparian ecosystems (Scott et al, 1999;Nippert et al, 2010;Pert et al, 2010). Thus, many studies have been undertaken over several decades to investigate the water use of GDEs in south-western North America (van Hylckama, 1970;Gay and Fritschen, 1979;Sala et al, 1996;Devitt et al, 1998;Goodrich et al, 2000a;Cleverly et al, 2002;Scott et al, 2004;Nagler et al, 2005b). Sunlight is plentiful in the south-western USA; thus, riparian GDEs are strong carbon sinks (Kochendorfer et al, 2011).…”
Section: The Gnangara Moundmentioning
confidence: 99%
“…Local reductions in the groundwater level may be caused by species that effectively exploit groundwater. Saltcedar can reach a lower water table and use more water per unit sapwood than several native species (Sala et al 1996;Cleverly et al 1997;Horton & Clark 2001). Shafroth et al (2000) found that saltcedar saplings were significantly less vulnerable than indigenous species to groundwater depletion.…”
Section: Phil Trans R Soc Lond B (2002)mentioning
confidence: 99%